2017
DOI: 10.1371/journal.pone.0180231
|View full text |Cite|
|
Sign up to set email alerts
|

Mountaintops phylogeography: A case study using small mammals from the Andes and the coast of central Chile

Abstract: We evaluated if two sigmodontine rodent taxa (Abrothrix olivacea and Phyllotis darwini) from the Andes and Coastal mountaintops of central Chile, experienced distributional shifts due to altitudinal movements of habitat and climate change during and after the Last Glacial Maximum (LGM). We tested the hypothesis that during LGM populations of both species experienced altitudinal shifts from the Andes to the lowlands and the coastal Cordillera, and then range retractions during interglacial towards higher elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…40°S was proposed for Abrothrix olivacea ( Smith, Kelt & Patton, 2001 ). Recently, Palma et al (2017) suggested for Phyllotis darwini and Abrothrix olivacea postglacial expansion from the lowlands and coastal areas towards the Andes; however, as this study considers a very small fraction of the whole species distributions (i.e., a sampled area restricted to 32° and 33° for species ranging from ca. 23° to 39° and ca.…”
Section: Introductionmentioning
confidence: 92%
“…40°S was proposed for Abrothrix olivacea ( Smith, Kelt & Patton, 2001 ). Recently, Palma et al (2017) suggested for Phyllotis darwini and Abrothrix olivacea postglacial expansion from the lowlands and coastal areas towards the Andes; however, as this study considers a very small fraction of the whole species distributions (i.e., a sampled area restricted to 32° and 33° for species ranging from ca. 23° to 39° and ca.…”
Section: Introductionmentioning
confidence: 92%
“…While some pioneer studies have already suggested that incorporating genetic information into SDMs improve model performance (Chardon et al, 2020;Palma et al, 2017), others have suggested that it does not improve model accuracy (Collart et al , 2020); Lecocq et al, 2019), thus reopening the debate on whether incorporating genetic information into SDMs can improve our understanding of species distribution. Noteworthy, these studies mainly focused on visual inspections from predicted maps to make comparisons of model performances or used general metrics of model performances (e.g.…”
Section: Implications For Forecasting Species Redistribution Under Fu...mentioning
confidence: 99%
“…Noteworthy, these studies mainly focused on visual inspections from predicted maps to make comparisons of model performances or used general metrics of model performances (e.g. Palma et al, 2017) systematically relying on presence-only data (Chardon et al, 2020) to validate their models and draw their conclusions, which may limit our abilities to evaluate the performance of geneticallyinformed SDMs. As far as we are aware, no study before ours has specifically tested the ability of genetically-informed SDMs to better explain the abundance of pollen found in the fossil records, providing truly independent evidence that genetically-informed SDMs outperform traditional SDMs in their abilities to detect potential refugia.…”
Section: Implications For Forecasting Species Redistribution Under Fu...mentioning
confidence: 99%
See 2 more Smart Citations